A little friendly advice - Vivian, Siobhan (New York : PUSH, 2008)
When Ruby's divorced father shows up unexpectedly on her sixteenth birthday, the week that follows is full of confusing surprises, including discovering that her best friend has been keeping secrets from her, her mother has not been truthful about the past, and life is often complicated.
Booklist
Publisher's Weekly
School Library Journal
Young Adult.
Young Adult
Keywords: Divorce -- Juvenile fiction; Friendship -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Photography -- Juvenile fiction; Secrecy -- Juvenile fiction; Divorce -- Fiction; Friendship -- Fiction; Interpersonal relations -- Fiction; Photography -- Fiction; Secrets -- Fiction; Divorce -- Fiction; Friendship -- Fiction; Interpersonal relations -- Fiction; Photography -- Fiction; Secrecy -- Fiction; Akron (Ohio) -- Juvenile fiction; Akron (Ohio) -- Fiction; Akron (Ohio) -- Fiction